HEAT MODELS OF ASTEROIDS AND THE YORP EFFECT - Golubov, O. (Одеські астрономічні публікації, 2014)
The Yarkovsky–O'Keefe–Radzievski–Paddack (YORP) effect is a torque of light pressure recoil forces acting on an asteroid. We show how this torque can be expressed as an integral of a universal function over the surface of an asteroid, and discuss generalizations of this expression for the case of non-Lambert’s scattering laws, non-convex shapes of asteroids, and non-zero heat conductivity. Then we discuss tangential YORP (TYORP), which appears due to uneven heat conductivity in stones lying on the surface of an asteroid. TYORP manifests itself as a drag, which pulls the surface in the tangential direction. Finally, we discuss relation and interplay between the normal YORP and the tangential YORP. Asteroids; dynamics – Galaxy; abundances; stars; late-type